2017
DOI: 10.1002/2016rs006242
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and measurement of electric fields of electrode-based through-the-earth (TTE) communication

Abstract: There are two types of through‐the‐earth (TTE) wireless communication in the mining industry: magnetic loop TTE and electrode‐based (or linear) TTE. While the magnetic loop systems send signal through magnetic fields, the transmitter of an electrode‐based TTE system sends signal directly through the mine overburden by driving an extremely low frequency (ELF) or ultralow frequency (ULF) AC current into the earth. The receiver at the other end (underground or surface) detects the resultant current and receives i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…It is interesting to note that there appears to be an optimum frequency around 90 Hz which shows the minimum attenuation caused by the channel. This finding is consistent with the finding reported in [16] that was based on the measurement results from a different coal mine. Similar to the received signal power, the interference power also decreases with frequency.…”
Section: Measured Channel Loss and Electromagnetic Interferencesupporting
confidence: 94%
See 2 more Smart Citations
“…It is interesting to note that there appears to be an optimum frequency around 90 Hz which shows the minimum attenuation caused by the channel. This finding is consistent with the finding reported in [16] that was based on the measurement results from a different coal mine. Similar to the received signal power, the interference power also decreases with frequency.…”
Section: Measured Channel Loss and Electromagnetic Interferencesupporting
confidence: 94%
“…For the receiver, signals from the wire connected to electrodes were directly fed into one of the analog input ports of the NI-DAC. More details about the measurement system can be found in [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring the three magnetic field components near the conductor, it was found that there is a coupling effect in the signal, which is caused by the current inside the slender conductor. This discovery can be used to predict the feasibility of strong penetration information transmission links in different settings and optimize the positions of the transmitting and receiving ends [3][4][5][6][7].…”
Section: Related Workmentioning
confidence: 99%
“…There are two types of through‐the‐Earth (TTE) wireless communication in the mining industry: magnetic loop through‐the‐Earth (TTE) and electrode‐based (or linear) TTE. While the electrode based TTE system sends a signal directly through the mine overburden by driving an extremely low frequency (ELF) or ultralow frequency (ULF) AC current into the Earth (Yan et al., 2017), the magnetic loop system sends a signal through magnetic fields. The receiver at the other end (underground or surface) detects the resultant magnetic fields and receives it as a voltage.…”
Section: Introductionmentioning
confidence: 99%